Designing an E-commerce Information System for “Sumatera Silver” Jewelry Store to Enhance Sales Efficiency - Shafira Shabirin; Khairi Budayawan; Kopnin Anton Andreevich (Journal of Hypermedia & Technology-Enhanced Learning, 2024)
This study explores the development of an E-commerce information system for the “Sumatera Silver” jewelry store, aimed at enhancing sales efficiency and overcoming the limitations of its current manual system. The manual system hindered operational efficiency, limiting market reach and preventing the business from tracking sales in real-time. The research employed the Prototype method to develop a user-centered system, incorporating real-time data tracking, automated sales reports, and improved customer accessibility. The system was designed using the CodeIgniter framework and adopts the MVC (Model, View, Controller) approach for modular, efficient system architecture. The results demonstrate that implementing the E-commerce system has significantly enhanced the store’s operational efficiency, enabling it to manage better customer transactions, sales data, and marketing outreach. The system also facilitates quicker and more accurate decision-making for store management by providing automated reporting and real-time sales analytics. This study concludes that adopting such a system offers substantial benefits for small- and medium-sized enterprises (SMEs), especially those looking to transition from traditional to digital sales models, ensuring competitiveness in the modern market. The findings underscore the importance of integrating digital solutions to streamline sales processes, improve customer satisfaction, and support business growth.